2016
DOI: 10.1111/1467-6427.12121
|View full text |Cite
|
Sign up to set email alerts
|

Talking About Versus Talking With: an experiential self of the therapist exercise for family therapy training

Abstract: This article describes an experiential self of the therapist exercise for use in family therapy training. It provides guidelines for instructors to integrate the activity into their courses including step‐by‐step directions, examples of processing questions, and potential readings to accompany the activity. The Talking About Versus Talking With exercise was designed to help family therapy students have a felt sense of some of the differences between individual and relational therapy. It provides trainers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Systems concepts are often difficult for students to learn because they can seem abstract, challenging to relate to on a philosophical level, and complicated to apply to real life family contexts (Piercy et al, 2016;Sheppard and Brew, 2005;Sude and Gambrel, 2016). Some trainees may struggle with systemic thinking because it can be contrary to linear or reductionist views of human behaviour.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Systems concepts are often difficult for students to learn because they can seem abstract, challenging to relate to on a philosophical level, and complicated to apply to real life family contexts (Piercy et al, 2016;Sheppard and Brew, 2005;Sude and Gambrel, 2016). Some trainees may struggle with systemic thinking because it can be contrary to linear or reductionist views of human behaviour.…”
Section: Rationalementioning
confidence: 99%
“…We have found that through the use of multimedia in the classroom, family therapy trainees can have more direct and concrete experiences with abstract systemic concepts, including those from structural family therapy. Teaching through examples, role plays, use of media, and other forms of experiential learning have been found to be beneficial to students (Nittoli and Guiffrida, 2017;Piercy et al, 2016;Sude and Gambrel, 2016). Previous authors have discussed ways to use movies to teach a variety of MFT course content, such as couple relationships (Shepard and Brew, 2005), addictions in the family (Hudock and Gallagher Warden, 2001), and human development (Croffie and Lertora, 2018).…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…This student gained empathy for what change may be like for her clients, something she could use with clients when she was in an asymmetrical position of power. Though this was a spontaneous response, trainers can also plan structured activities in advance to help trainees value their clients' experiences in similar ways (see Sude & Gambrel, ).…”
Section: Contextual Skills For Trainersmentioning
confidence: 99%